(untitled) - Ros Jay; Ros Jay (London,Boston, 1998)
A direct working manual to maximize useful practical tips and hints. Explaining ways to save money on buying in marketing information or expertise, this text also demonstrates many of the skills that companies with higher budgets would farm out. It includes anecdotes and examples which draw on the experience of people who have achieved successthrough low budget marketing themselves
Keywords: Marketing; Marketing; Marketing